PENGARUH NPF, BOPO DAN PEMBIAYAAN BAGI HASIL TERHADAP PROFITABILITAS BANK UMUM SYARIAH DI INDONESIA - Vista Qonitah Qotrun Nuha; Ade Sofyan Mulazid (al-Uqud : Journal of Islamic Economics, 2018)
This study aims to determine the effect of non performing financing, operational expenses ratio, and profit sharing financing to return on assets partially and simultaneous at Sharia Bank period December 2011- December 2015. There is 7 banks that fulfilled the criteria BCA Syariah, BNI Syariah, BRI Syariah, Mandiri Syariah, Mega Syariah, Muamalat Bank, Bank Panin Sharia. The analytical method that used in this study is balanced panel. The selected model is Common Effect that tested with F test and t-test with significancy level 5%. Based on the result of F test, known that NPF, operational expenses ratio and proft sharing financing affect simultaneously of return on assets. Based on the result of t-test, NPF and profit sharing financingdoes not affect partially of return on assets.